Metabolic syndrome, not menopause, is a risk factor for hypertension in peri-menopausal women - Gyu Chul Oh; Kee Soo Kang; Chan Soon Park; Ho Kyung Sung; Kyoung Hwa Ha; Hyeon Chang Kim; Sungha Park; Sang Hyun Ihm; Hae-Young Lee (BMC, 2018)
Abstract Background It has been long debated whether menopause itself is a risk factor for hypertension in peri-menopausal women. We aimed to assess the association between menopause and hypertension, and whether metabolic syndrome (MetS) has an influence on its effect. Methods Data for 1502 women aged 42 to 53 from the Korean Genome and Epidemiology Study (KoGES) database were retrospectively analyzed. The KoGES database consists of 10,038 participants, of which 52.6% (5275) were female. Subjects were followed up for 4 years, and compared according to menopausal status. Additionally, 1216 non-hypertensive subjects were separately analyzed to assess whether a change in menopausal status was associated with development of hypertension. Results The prevalence of hypertension, diabetes, and MetS for menopausal and non-menopausal subjects at baseline was 24.4% vs. 16.7%, 5.8% vs. 2.9%, and 25.4% vs. 16.6%, respectively (p < 0.01 for all comparisons). Among non-hypertensive subjects at baseline, prevalence of hypertension at 4-year follow-up was 9.4%, 19.7%, and 13.1% for non-menopausal, those who became menopause during follow-up, and those who were menopause at baseline, respectively. Development of hypertension was positively correlated with MetS (HR 3.90, 95% CI 2.51-6.07) and increased BMI (HR 1.09, 95% CI 1.03-1.16), while association with menopause was not significant. Conclusions Menopause is closely associated with increased incidence of hypertension, but the increase may not be attributable to menopause itself but to increased prevalence of MetS.